Reform of juvenile criminal justice: a special focus on the effectiveness of correctional treatment in approved schools / Chong Phaik Kee - Chong, Phaik Kee (2003)
It is now an old adage that juvenile justice reform is no sport for the short-winded. Juvenile law reform is both an incomplete achievement and an ongoing process, where the more progressive and the regressive forces of the different professionals and citizen groups skirmish between soft-line and hard-line extremes, contesting the need for further legal checks and balances. The violence of some juvenile offenders in this country is arousmg growing concern. Concerns about the welfare of the young have too often been seen as in conflict with the aims of protecting the public, punishing offences and preventing offending. This confusion creates real practical difficulties for practitioners and has contributed to the loss of public confidence in the juvenile justice system. Policy makers are caught in the crossfire between society's desire to nurture its youth and the imperative to punish its criminals. It is especially difficult to choose between rehabilitation and 'get tough approaches'. To reform juvenile criminal justice in this country, which is approximately 55 years old, it is imperative to respond to public safety concerns and simultaneously advance improved treatment for juvenile offenders. This research project addresses the above concern. It discusses general patterns and trends in crimes committed by children - trends revealed by arrest data and other sources. It reviews the historical context of the juvenile justice system and analyses recent legislative reforms that give rise to a new justice system for children. It reviews the search for a new ' rehabilitative ideal' that could provide a foundation for a new system of correctional treatment for juveniles who had to be institutionalised. This research project has a special focus on the correctional treatment in approved schools and their operations in more detail. This is a field that demands our attention.